Who profits from agroecology to secure food and nutrition? On access of women to markets and assets - Ume, Chukwuma; Nuppenau, Ernst-August; Domptail, Stéphanie Eileen (Frontiers in Sustainable Food Systems, 2023)
In contrast to a large body of literature linking agroecology to food security through sustainable agronomic practices, research on how agroecology enhances smallholder farmers’ access to productive resources, yet necessary for food security and nutrition, is sparse in Africa. Literature does not consider the fact that agroecology practices are often adopted via entering a group that provides corresponding knowledge, network and possibly markets. We investigate the case of an agroecology group operating parallel to the dominant agri-industrial food system in Southeast Nigeria. We ask: who are the agroecology farmers? Do they improve their food status in comparison to conventional smallholders operating in the commodity oriented agro-industrial system? Who appears to benefit most among agroecology farmers? To provide answers to these questions, we collected data from 334 smallholder farmers (comprising 111 agroecology farmers and 223 non-agroecology farmers) through a stratified cluster sampling process. Descriptive statistics of our data showed that women make up 89% of the agroecology farmers in the group. We found that in both the agroecology and the conventional groups, women farmers had little access to land, even lower ownership of land, little exposure to extension services, and no access to financial credits. Thus, the sample of female farmers we addressed consists of marginal persons who operate at the margins of the capital and input-based networks and agricultural production. In contrast to the expectation of conventional hypotheses, we show that on average, agroecology farmers had lower food insecurity experiences and higher observed dietary diversity scores. Exploring more detail within the agroecology group via a quantile semi-parametric propensity score matching, we further show that women left out of conventional extension services benefit more from being in the agroecology group. Similarly, the increase in food security and nutrition was highest among those farmers who balance self-provisioning and market as food sources compared to strategies pursued mainly by one of these two sources. To these farmers, mostly women, the agroecology group provides alternative to access important resources and knowledge that they ordinarily would not have accessed being in the capitalistic food system, and which enables them to reach their nutrition goals. Our study supports a conceptualization of agroecology as an interdependency between agroecological agronomic practices, reciprocity and autonomy-fostering social innovations.